Ethical road map through the covid-19 pandemic. (21st May 2020) - Fritz, Zoe; Huxtable, Richard; Ives, Jonathan; Paton, Alexis; Slowther, Anne Marie; Wilkinson, Dominic
Abstract : We must follow the ethics, not just the science